Bark beetles as lidar targets and prospects of photonic surveillance. Issue 4 (14th December 2020) - Li, Meng; Jansson, Samuel; Runemark, Anna; Peterson, Jonathan; Kirkeby, Carsten Thure; Jönsson, Anna Maria; Brydegaard, Mikkel
Abstract: Forestry is raising concern about the outbreaks of European spruce bark beetle, Ips typographus, causing extensive damage to the spruce forest and timber values. Precise monitoring of these beetles is a necessary step towards preventing outbreaks. Current commercial monitoring methods are catch‐based and lack in both temporal and spatial resolution. In this work, light scattering from beetles is characterized, and the feasibility of entomological lidar as a tool for long‐term monitoring of bark beetles is explored. Laboratory optical properties, wing thickness, and wingbeat frequency of bark beetles are reported, and these parameters can infer target identity in lidar data. Lidar results from a Swedish forest with controlled bark beetle release event are presented. The capability of lidar to simultaneously monitor both insects and a pheromone plume mixed with chemical smoke governing the dispersal of many insects is demonstrated. In conclusion, entomological lidar is a promising tool for monitoring bark beetles. Abstract : Precise monitoring of European spruce bark beetle, Ips typographus, is necessary for fighting bark beetle infestation early. In this work, optical properties, wing thickness, and WBF of bark beetles are reported, and these parameters infer target identity in lidar data. Lidar results from a Swedish forest with a controlled bark beetle release event are presented. We concluded that our entomological lidar is a promising tool for remote monitoring bark beetles.